Culture and sensitivity patterns of bacteriological agents in children admitted to a tertiary care hospital (Journal of Fatima Jinnah Medical University, 2021)
Background: Culture from various infected body fluids is one of the commonly used investigations to establish the etiology of infections and helps clinicians to select appropriate antimicrobial therapy. This study is aimed to determine the culture and sensitivity patterns of bacteriological agents grown in children admitted to a tertiary care center.Patients and methods: This descriptive cross-sectional study was conducted at the Department of Pediatric Medicine, The Children’s Hospital and the Institute of Child Health, Lahore from April 2019 to December 2019. All admitted children of age £ 15 years who fulfilled the criteria of systemic inflammatory response syndrome and sepsis were enrolled in the study. Blood and other body fluids were cultured in appropriate medium as indicated. Profile of microorganisms grown and their sensitivity patterns were noted and recorded on a predesigned data sheet. Statistical analysis was performed by SPSS v.22.Results: A total of 500 patients were enrolled in the study. Eighty-three of them (16.6%) had growth of different microorganisms on culture and were further analyzed. Total 58 of these 83 (69.87%) were
Keywords: Culture; Pus; Antibiotics; Sensitivity; Resistance; Children; Blood; Urine